KORELASI ANTARA AGREGASI TROMBOSIT TERHADAP ADENOSINE DIPHOSPHATE DENGAN KELUARAN FUNGSIONAL STROKE ISKEMIK AKUT - Bambang Kusnardi, Moh. Hasan Machfoe (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION PLATELETS IS ONE OF THE TARGET TREATMENTS FOR THROMBOTIC INFARCTION STROKE ADENOSINE DIPHOSPHATE ADP IS ONE OF THE CHEMICALS THAT CAUSE PLATELET AGGREGATION AND THROMBUS THAT ALSO AGGRAVATE THE ONSET OF ISCHEMIA IN THE BRAIN